Experimental Investigation on Interfacial Behavior of Spiral Waste Iron Lathe Fibers Using Pull Out Test - Arum Dwicahyani; Ahmad Ghufron; Bagas Wahyu Adhi; Dhonna Meylida; Betty Hariyani (Journal of Civil Engineering, Planning and Design, 2026)
Fiber-reinforced cementitious composites exhibit enhanced ductility, crack resistance, and energy dissipation due to fiber–mortar interaction within the interfacial transition zone (ITZ). However, the interfacial behavior of irregular waste-derived fibers, particularly spiral-shaped iron lathe waste, remains insufficiently understood. This study experimentally investigates the bond performance and failure mechanisms of spiral waste iron lathe fibers embedded in a mortar matrix using single-fiber pull-out testing. Mortar specimens with a cement-to-sand ratio of 1:2 was prepared, and single fibers with a diameter of 1 mm were symmetrically embedded within double-cube specimens. Pull-out tests were conducted under displacement-controlled loading to obtain load–slip responses. Bond stress and energy dissipation were calculated from the experimental data, while mean, standard deviation, and coefficient of variation (CV) were used to assess data homogeneity. The results indicate that fiber–mortar interaction is governed by adhesion, friction, and mechanical interlocking mechanisms. Three failure modes were observed, namely pull-out, fiber rupture, and mixed failure, demonstrating strong sensitivity of interfacial behavior to local bonding conditions. Pull-out failure exhibits gradual post-peak softening and higher energy dissipation, whereas fiber rupture shows a sudden load drop and lower energy absorption capacity. All measured parameters are statistically homogeneous with CV values below 20%, confirming data reliability. This study demonstrates that irregular waste lathe fibers can effectively contribute to crack-bridging and energy dissipation, highlighting their potential as sustainable reinforcement in cement-based composites.